Resident as Teacher Curriculum - Heather Harrell; Joyce Wipf; Paul Aronowitz; Joseph Rencic; David Gary Smith; Susan Hingle; Donald Bordley; Paul Mendez; Eric Green; Erica Friedman; Tayloe Loftus; Richard Simons; et al. (Association of American Medical Colleges, 2015)
Abstract This is a series of 10 modules developed to instruct residents how to teach within the constraints of a busy workday. The content emphasizes the application of teaching principles to common occurrences in an inpatient setting, such as oral presentations, reviewing progress notes, working up a new patient, and performing physical examinations. They are designed to have minimal didactic content and focus more on promoting discussions and providing skills practice. They are intended to be adapted to meet individual programs' needs and can also supplement existing resident-as-teacher programs. The authors have used these modules successfully at their own institutions and have received positive feedback from program directors who have used these modules successfully at their own institutions. They have been used as part of a formal resident-as-teacher program (both longitudinal programs and limited half-day workshops) and have been used to reinforce concepts later in training. The cases have also been incorporated into locally-developed modules as springboards for small-group discussion and skills practice.